Remote sensing and identification of volcanic plumes using fixed‐wing UAVs over Volcán de Fuego, Guatemala. Issue 7 (24th July 2019) - Schellenberg, Ben; Richardson, Tom; Watson, Matt; Greatwood, Colin; Clarke, Robert; Thomas, Rick; Wood, Kieran; Freer, Jim; Thomas, Helen; Liu, Emma; Salama, Francis; Chigna, Gustavo
Abstract: This paper describes a series of proof‐of‐concept Beyond Visual Line Of Sight unmanned aerial vehicle flights which reached a range of up to 9 km and an altitude of 4, 410 m Above Mean Sea Level over Volcán de Fuego in Guatemala, interacting with the volcanic plume on multiple occasions across a range of different conditions. Volcán de Fuego is an active volcano which emits gas and ash regularly, causing disruption to airlines operating from the international airport 50 km away and impacting the lives of the local population. Collection of data from within the plume develops scientists' understanding of the composition of the volcano's output and is of use to scientists, aviation, and hazard management groups alike. This paper presents preliminary results of multiple plume interceptions with multiple aircraft, carrying a variety of sensors. A plume‐detection metric is introduced, which uses a combination of flight data and atmospheric sensor data to identify flight through a volcanic plume. Future work will develop the automation of plume tracking such that reliable scientific data sets can be gathered in a robust manner.